EULAR points to consider for the management of difficult-to-treat rheumatoid arthritis - Nagy, György; Roodenrijs, Nadia M T; Welsing, Paco M J; Kedves, Melinda; Hamar, Attila; van der Goes, Marlies C; Kent, Alison; Bakkers, Margot; Pchelnikova, Polina; Blaas, Etienne; Senolt, Ladislav; Szekanecz, Zoltan; et al. (Annals of the rheumatic diseases, 2022)
OBJECTIVE: To develop evidence-based European Alliance of Associations for Rheumatology (EULAR) points to consider (PtCs) for the management of difficult-to-treat rheumatoid arthritis (D2T RA). METHODS: An EULAR Task Force was established comprising 34 individuals: 26 rheumatologists, patient partners and rheumatology experienced health professionals. Two systematic literature reviews addressed clinical questions around diagnostic challenges, and pharmacological and non-pharmacological therapeutic strategies in D2T RA. PtCs were formulated based on the identified evidence and expert opinion. Strength of recommendations (SoR, scale A-D: A typically consistent level 1 studies and D level 5 evidence or inconsistent studies) and level of agreement (LoA, scale 0-10: 0 completely disagree and 10 completely agree) of the PtCs were determined by the Task Force members. RESULTS: Two overarching principles and 11 PtCs were defined concerning diagnostic confirmation of RA, evaluation of inflammatory disease activity, pharmacological and non-pharmacological interventions, treatment adherence, functional disability, pain, fatigue, goal setting and self-efficacy and the impact of comorbidities. The SoR varied from level C to level D. The mean LoA with the overarching principles and PtCs was generally high (8.4-9.6). CONCLUSIONS: These PtCs for D2T RA can serve as a clinical roadmap to support healthcare professionals and patients to deliver holistic management and more personalised pharmacological and non-pharmacological therapeutic strategies. High-quality evidence was scarce. A research agenda was created to guide future research.
Keywords: Medication Adherence; ultrasonography; Humans; Arthritis, Rheumatoid; antirevmatika; inflammation; Patient Education as Topic; Hepatitis C; komorbidita; lidé; rheumatoid; revmatoidní artritida; určení symptomu; Cognitive Behavioral Therapy; hepatitida C; Comorbidity; hepatitida B; Hepatitis B; Antirheumatic Agents; vzdělávání pacientů jako téma; kognitivně behaviorální terapie; Exercise; cvičení; arthritis; adherence k farmakoterapii; fibromyalgia; Symptom Assessment